Massive open online courses for health worker education in low- and middle-income countries: a scoping review - Nieder, Jessica; Schwerdtle, Patricia; Sauerborn, Rainer; Barteit, Sandra (Frontiers in Public Health, 2022)
BackgroundMassive Open Online Courses (MOOCs) have the potential to improve access to quality education for health care workers (HCWs) globally. Although studies have reported on the use of MOOCs in low- and middle-income countries (LMICs), our understanding of the scope of their utilization or access barriers and facilitators for this cohort is limited. We conducted a scoping review to map published peer-reviewed literature on MOOCs for HCW education in LMICs. We systematically searched four academic databases (Scopus, Web of Science, PubMed, ERIC) and Google Scholar, and undertook a two-stage screening process. The analysis included studies that reported on MOOCs relevant to HCWs' education accessed by HCWs based in LMICs.ResultsThe search identified 1,317 studies with 39 studies included in the analysis, representing 40 MOOCs accessed in over 90 LMICs. We found that MOOCs covered a wide range of HCWs' including nurses, midwives, physicians, dentists, psychologists, and other workers from the broader health care sector, mainly at a post-graduate level. Dominant topics covered by the MOOCs included infectious diseases and epidemic response, treatment and prevention of non-communicable diseases, communication techniques and patient interaction, as well as research practice. Time contribution and internet connection were recognized barriers to MOOC completion, whilst deadlines, email reminders, graphical design of the MOOC, and blended learning modes facilitated uptake and completion. MOOCs were predominantly taught in English (20%), French (12.5%), Spanish (7.5%) and Portuguese (7.5%). Overall, evaluation outcomes were positive and focused on completion rate, learner gain, and student satisfaction.ConclusionWe conclude that MOOCs can be an adequate tool to support HCWs' education in LMICs and may be particularly suited for supporting knowledge and understanding. Heterogeneous reporting of MOOC characteristics and lack of cohort-specific reporting limits our ability to evaluate MOOCs at a broader scale; we make suggestions on how standardized reporting may offset this problem. Further research should focus on the impact of learning through MOOCs, as well as on the work of HCWs and the apparent lack of courses covering the key causes of diseases in LMICs. This will result in increased understanding of the extent to which MOOCs can be utilized in this context.